Physical studies of denatured tRNA2Glu from Escherichia coli. - Bina-Stein, M (1976)
We have examined the 270 MHz nuclear magnetic resonance spectrum and relaxation kinetic behavior of tRNA2Glu (E. coli) in the absence of Mg++, a condition which produces an inactive form of this tRNA. The results show that the denatured form has about five fewer proton resonances in the region from -12 to -15 ppm. Relaxation kinetic measurements reveal that the denatured conformer contains three separately melting helices. The results support a model in which the tertiary structure and dihydrouridine helix characteristic of the native form are unfolded in the denatured state, and are replaced by an altered tertiary structure. The acceptor stem, anticodon, and TpsiC helices are intact in this model for the denatured conformation. The optical changes that accompany melting of the denatured tertiary structure are faster than 10 musec.